BREAKING SEED DORMANCY USING CHEMICAL, PHYSICAL, AND ORGANIC SCARIFICATION METHODS ON THE GROWTH OF AREN SEEDS (Arenga pinnata Merr.) - Hetty Lisma Evianti Manurung; Rahmad Setia Budi; Murni Sari Rahayu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Prolonged seed dormancy is an obstacle in the provision of quality seedlings. Therefore, this study was conducted to accelerate the germination process of Arenga pinnata Merr. seeds through various treatments. This study aims to evaluate the response of chemical, physical, and organic dormancy breaking on the growth and development of Arenga pinnata Merr. seeds. The method used was a Non-Factorial Complete Randomized Design with seven treatments: seed soaking in 3% H₂SO₄ solution (6 hours), 0.5% KNO₃ (24 hours), 3% HCl (6 hours), sanding (sandpaper), 100% red onion extract (24 hours), 100% palm sap (24 hours), and 100% coconut water (24 hours). The results showed that seed soaking in 3% HCl or sandpaper abrasion yielded the best results in terms of germination rate, although there was no statistically significant effect; these treatments also successfully reduced the dormancy period of palm seeds. Additionally, soaking with 100% palm sap produced the tallest plants at 8 MST and 12 MST. This study is expected to provide useful information for the development of more efficient and practical palm seedling propagation technology.